Pseudomonas aeruginosa: fixação biológica do nitrogênio, promoção de crescimento, sanidade e produção de arroz de terras altas no Estado do Maranhão - Bitu, Pedro Ivo Menezes (2020)
We evaluated the capacity of the species Pseudomonas aeruginosa in terms of: fixing atmospheric nitrogen, promoting growth, health and rice production, under a system of cultivation in highlands, in Maranhão, Brazil. Initially, uniform collections of upland rice plants were carried out in the municipalities of Maranhão: São Mateus, Igarapé do Meio, Bacabal, Belágua, Viana, Itapecuru, São Bento, Presidente Juscelino, São Benedito do Rio Preto, Urbano Santos, Matinha, Arari and Governador Newton Bello. Then, bacterial isolation of the leaves and roots of rice was carried out, for later identification of the isolates. The activity of the nitrogenase enzyme and the production of indole acetic acid of the isolates were evaluated respectively by the acetylene reduction method and by the colorimetric method. For field experiments, only the two isolates with the highest nitrogenase activity were considered. Two experiments were installed in two consecutive years, both in randomized blocks, with seven treatments and four repetitions in Santa Rita-Ma (2018), and eight treatments and four repetitions in Pirapemas-MA (2019). The treatments consisted of the microbiolization of rice seeds cultivar primavera, with two strains of Pseudomonas aeruginosa, with and without association with the spraying of the bacterial solution and NPK fertilization. In both experiments, the control treatments were designated as absolute control (without microbiolization and fertilizer) and fertilized. 33 bacterial rice isolates were obtained, all identified as Pseudomonas aeruginosa. The isolates identified as P. aeruginosa showed phylogenetic proximity to the species Comamonas sediminis, Stenotrophomonas tumulicula, S. maltophhilia, Pseudomonas hibscicola, Raoultella ornithinolytica, Celvibrio japonicus and Escherichia coli. We verified the activity of the nitrogenase enzyme in 15 of the P. aeruginosa isolates, 6 with ARA greater than 1, with a maximum of 26, 66 nmolC2H4 / h. 6 isolates with ARA greater than 1 used, produced indole acetic acid, with variations from 18.00 to 18.23 µg.L1.There was a significant effect of the bacteria on germination (%) and initial height of the plants (cm), mass of 1000 grains (g), percentage of whole grains, dry matter of the plant (g), number of panicles, total height in the end of the cycle (m), nitrogen content in the aerial part and grains of rice and reduction in the severity of diseases brown spot, leaf spot and scald. The treatments under the influence of P. aeruginosa were equal or superior to the fertilized control, showing the potential of using the bacterium as an economical and ecological alternative to the excessive use of fertilizers and pesticides.